TINJAUAN PERENCANAAN GELAGAR BETON PRATEGANG PADA JEMBATAN BAKONGAN KECAMATAN PERMATA KABUPATEN BENAR MERIAH - Ghali Hari (Politeknik Negeri Lhokseumawe, 2016)
Bakongan bridge located in Bakongan village, Permata Subdistrict, Bener Meriah District. Based on the characteristics of the river, the bridge isplanned to Bakongan spans 13,6 meters long and 6 meters width. Girder longitudinal direction planned for the bridge is prestressed concrete girder type of post tension with the imposition of standard rules RSNI T-02-2005, RSNI T-12-2004 and Construction Manual 021/BM/201 J . Jn the early stages of planning done preliminary design to determine the dimensions of the main bridge, the calculation of the secondary structure are used as load analysis that occurs, the control voltage that occurs in the structure, post-tensile prestressing loss, sectional capacity, control deflection, and depiction. Quality of concrete used was Jc = 45 MPa, tendon used is seven strand wire with a diameter of 9,3 mm inch diameter 51 mm shells tendon. Voltage tendonfpu = 1860 MPa, quality threaded steel reinforcement isfY = 320 MPa, and quality plain steel reinforcement isfY = 240 MPa. Moments that occur in the calculation of girder 1502,0967 KNM combination III. Number of tendons obtained from the calculation is 5 to 35 pieces offruit on each strand tendons. Total loss of prestressing force obtained at 817,54 MPa or 34 %. Principal reinforcement used Æ13 mm, Æ10-shear reinforcement used in the staging area 100 mm and g 10-600 mm in thefield area. Ultimate moment capacity of prestressed beams 3629664KN/m combination Ill of calculation. Greatest deflection is 0.0151 meters caused by a combination JV. Keywords: Concrete prestressed, Post-tension girder, tendons, reinforcement